Analisis Pengaruh Sektor Basis dan Non Basis Terhadap Pertumbuhan Ekonomi di Provinsi Lampung: Indonesia - Wardhani, Natasya Ayu (Universitas Negeri Surabaya, 2023)
The purpose of this study was to determine the effect of the base and non-base sectors on economic growth in Lampung province. This research method uses Location Quetiene (LQ) analysis and Klassen Typology analysis. The results of this study are that the economic growth and good contribution of Lampung Province to the national economy cannot be separated from economic development carried out by smaller areas in Lampung Province, namely districts and cities. According to the Central Bureau of Statistics (2021) the agriculture, forestry and fisheries sectors are one of the primary economic sectors that make the highest contribution to the GRDP of Lampung Province for the 2019-2021 period, which is always greater than 35%.